2013
DOI: 10.1177/0194599813515184
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Physical Injury on Otovestibular and Cognitive Symptomatology following Blast Exposure

Abstract: Blast-exposed individuals who sustained severe extremity injuries reported significantly fewer cognitive and vestibular symptoms. In the aftermath of a blast, those who can walk away may have still sustained a significant injury. Specifically, they may suffer more long-term cognitive and vestibular symptoms than those with severe physical injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Noise overexposure can also damage the vestibular periphery (see summary by Stewart et al [ 27 ]). Preclinical work based on different animal models has demonstrated that, depending upon the noise characteristics, noise overexposure often leads to cellular damage in the peripheral vestibular system with a well-characterized effect on the response of otolith organs [ 28 , 29 , 30 , 31 ]. Studies using vestibular evoked myogenic potentials (VEMPs) [ 31 , 32 , 33 , 34 ] have provided evidence of the same in individuals with NIHL and in military veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Noise overexposure can also damage the vestibular periphery (see summary by Stewart et al [ 27 ]). Preclinical work based on different animal models has demonstrated that, depending upon the noise characteristics, noise overexposure often leads to cellular damage in the peripheral vestibular system with a well-characterized effect on the response of otolith organs [ 28 , 29 , 30 , 31 ]. Studies using vestibular evoked myogenic potentials (VEMPs) [ 31 , 32 , 33 , 34 ] have provided evidence of the same in individuals with NIHL and in military veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Although football injuries receive the most attention in the press, 14 there is a substantial literature regarding the occupational incidence of mTBI from the military alone. [1][2][3][4][5][15][16][17] …”
Section: Epidemiologymentioning
confidence: 99%
“…Following these injuries, there are varying degrees of physical, cognitive, and emotional impairment that may impede function (Scherer and Schubert 2009). Visual and vestibular impairments such as blurry vision, postural imbalance, vertigo, headache, and dizziness constitute the most common sequela seen in this population (Johnson et al 2014;Hoffer et al 2004). These impairments contribute to degradation of function by limiting activity and restricting participation in community and duty-related tasks.…”
Section: Introductionmentioning
confidence: 99%